2015
DOI: 10.1039/c5qi00091b
|View full text |Cite
|
Sign up to set email alerts
|

DFT and TD-DFT studies of electronic structures and one-electron excitation states of a cyanide-bridged molecular square complex

Abstract: The electronic structures of a cyanide bridged Fe-Co molecular square, [Co 2 Fe 2 (CN) 6 (tp*) 2 (dtbbpy) 4 ]-(PF 6 ) 2 ·2MeOH (1) (tp* = hydrotris (3,5-dimethylpyrazol-1-yl) borate, dtbbpy = 4,4'-di-tert-butyl-2,2'bipyridine), which exhibits thermal and photo-induced two-step charge-transfer induced spin transitions (CTIST), are investigated in detail by density functional theory (DFT) and time-dependent (TD) DFT calculations. For the three phases observed in the experiment, three different model structures a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 49 publications
0
16
0
1
Order By: Relevance
“…On the other hand, one unpaired electron in the t 2g orbital of the hs Co(II) ion ] tetranuclear complex of 2 in detail by density functional theory and suggested weak ferromagnetic interactions operative between hs Co(II) and ls Fe(III) ions in the tetranuclear core. 76 On the other hand, Lescouëzec et al reported the first cyanidebridged Co-Fe 1D chain system exhibiting slow magnetic relaxation in 2003, which is due to substantial ferromagnetic interactions between hs Co(II) and ls Fe(III) ions and Ising type magnetic anisotropy in the 1D structure. 77 The first photoswitchable slow magnetic relaxation was reported on a cyanidebridged 1D Co-Fe system in 2012 by Sato and coworkers.…”
Section: Light-induced Magnetization In Molecular Pbasmentioning
confidence: 99%
“…On the other hand, one unpaired electron in the t 2g orbital of the hs Co(II) ion ] tetranuclear complex of 2 in detail by density functional theory and suggested weak ferromagnetic interactions operative between hs Co(II) and ls Fe(III) ions in the tetranuclear core. 76 On the other hand, Lescouëzec et al reported the first cyanidebridged Co-Fe 1D chain system exhibiting slow magnetic relaxation in 2003, which is due to substantial ferromagnetic interactions between hs Co(II) and ls Fe(III) ions and Ising type magnetic anisotropy in the 1D structure. 77 The first photoswitchable slow magnetic relaxation was reported on a cyanidebridged 1D Co-Fe system in 2012 by Sato and coworkers.…”
Section: Light-induced Magnetization In Molecular Pbasmentioning
confidence: 99%
“…As shown in Table 1, the changes in the transition temperature (T 1/2 )i ndicate that the tendency of the MMCT process from the {Fe II LS (m-CN)Co III LS }s tate to the {Fe III LS (m-CN)Co II HS }s tate is different, which can be understood in terms of the molecular orbital energy gap of the diamagnetic {Fe II LS (m-CN)Co III LS }s pecies.T hus,D FT calculations were performed by using the hybrid B3LYP functional based on the LT structure of 1·BF 4 and 1·PF 6 -b determined by X-ray diffraction. Thecomputed energy gap (DE)between occupied Fe orbitals and unoccupied Co orbitals [36] In addition, the changes in intermolecular p···p interactions result in different bend angles of the Co-NCbonds and octahedral distortions around the Co center,w hich may be intrinsic of different MMCT behaviors.The distortion degree can be evaluated by the parameters S (the sum of j 90Àa j for the 12 cis-N-Co-N angles around the Co center) and CShM Co (the continuous shape measure relative to the ideal octahedron of the Co center). As shown in Table 1, the values of S and CShM Co obtained for 1·PF 6 Figure S22), can be invoked as responsible for the lowest transition temperature of Table S2, the values of CShM Fe for 1·PF 6 Figure 6a).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Thus, DFT calculations were performed by using the hybrid B3LYP functional based on the LT structure of 1⋅BF 4 and 1⋅PF 6 ‐β determined by X‐ray diffraction. The computed energy gap (Δ E ) between occupied Fe orbitals and unoccupied Co orbitals was 2.07 and 1.54 eV for 1⋅BF 4 and 1⋅PF 6 ‐β , respectively (Figure ). A smaller energy gap can induce charge transfer from Fe‐based occupied orbitals to Co‐based unoccupied orbitals more easily, which affords a lower transition temperature.…”
Section: Resultsmentioning
confidence: 99%